Non-linear 2D ray tracing model of the propagation of acoustic waves in the atmosphere - Mialle, Pierrick (My University, 2004)
The infrasound propagation in the atmosphere over large distance is a complex topic. The scientific community is dealing with infrasound for years now and a large number of measurements has been performed. However accurate models, to understand those experiments, are still awaited. Since 1996, the Comprehensive Test Ban treaty has been signed. It opened the path toward a further understanding of the infrasound propagation. The present work deals with ray tracing model to simulate the infrasound propagation and especially the non linear effects caused by strong explosions. In order to simulate those non linear effects, a perturbation method of the sound velocity has been used. This perturbation is based on the estimation of the overpressure created by the explosion along the ray. The model also needs to take into account the influence of the atmosphere (temperature, density, wind, sound profiles...etc) which is a complex medium. The non linear ray tracing model developed simulates the infrasound propagation in a two dimensional atmosphere with a specific paraxial ray tracing method. If the correlation between simulation and measurement shows unexpected results in the shadow zone and for the propagation time, it is also true that the non linear implementation creates numerical obstacles at the caustic points (i.e. focalization of energy). The developed model has created high expectations for operational purposes such as the localization of infrasound sources (mainly nuclear tests, but also rockets take-off, volcanic eruptions...).
Keywords: Samhällsbyggnadsteknik; Civil Engineering